2018
DOI: 10.1177/2192568218789115
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Treating Cervical Adjacent Segment Disease by Anterior Cervical Discectomy and Fusion Versus Total Disc Replacement: A Systematic Review and Meta-Analysis

Abstract: Study Design: Systematic review and meta-analysis. Objective: To compare clinical outcomes of all available adjacent segment disease (ASD) cohorts being treated by either anterior cervical discectomy and fusion (ACDF) or total disc replacement (TDR). Methods: We followed the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines for systematic reviews. Searches of electronic databases from inception to August 2017 identified 349 articles for screening. Data was extracted and ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
1
6
1
Order By: Relevance
“…In a recent systematic review and meta-analysis, the authors discovered shorter operative times among patients receiving CDR, in contrast to our findings. 19 However, estimated blood was statistically similar for both surgeries, as we reported. Similarly, in a meta-analysis by Wu et al comparing multiple-level CDR versus ACDF, no such difference was found for operative duration or blood loss among the two procedures.…”
Section: Perioperative Outcomessupporting
confidence: 79%
“…In a recent systematic review and meta-analysis, the authors discovered shorter operative times among patients receiving CDR, in contrast to our findings. 19 However, estimated blood was statistically similar for both surgeries, as we reported. Similarly, in a meta-analysis by Wu et al comparing multiple-level CDR versus ACDF, no such difference was found for operative duration or blood loss among the two procedures.…”
Section: Perioperative Outcomessupporting
confidence: 79%
“…Several reports unanimously demonstrated the clinical efficacy and safety of such a strategy. 41,58,59 However, studies with larger patient numbers and longer follow-up are mandatory to compare the efficacy of treating ASD with CDA and ACDF. Also, more studies are needed to elucidate the best combination strategy for different designs of the hybrid construct when it comes to different spondylotic conditions among various levels.…”
Section: Hybrid Cda-acdf Surgerymentioning
confidence: 99%
“…Bin et al 53 reported on the treatment of 32 patients who had ASD treated with a CDA at the adjacent level and found good clinical outcomes with a maintained range-of-motion at the CDA level. In a systematic review by Lu et al, 54 the treatment of adjacent-level disease by ACDF versus CDA found that CDA had similar surgical and postoperative outcomes to the treatment of ASD as ACDF.…”
Section: Multi-level (3-level or 4-level) Cdamentioning
confidence: 99%